KOORDINASI SERIKAT PEREMPUAN INDONESIA (SERUNI) DENGAN ASIA PACIFIC FORUM ON WOMEN, LAW AND DEVELOPMENT (APWLD) DALAM ISU HAK BURUH PEREMPUAN DI INDONESIA TAHUN 2017-2018 - Nadia Zahra Rahmadhani; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT This research will discuss about the results of Asia Pacific Forum on Women, Law and Development (APWLD)’s coordinated campaigns with its Indonesian transnational advocacy network, Serikat Perempuan Indonesia (SERUNI). The case studied is the implementation of APWLD’s programs about women's labour rights, Breaking Out of Marginalization (BOOM) and Labour & Migration (L&M), in Indonesia in 2017-2018. This research is a qualitative research that reviews an event based on social patterns, interactions between communities, and its social influences. The data collection methods are interviews and document analysis. The perspective used in analyzing the topic is constructivism with Keck and Sikkink’s Transnational Advocacy Network (TAN) theory. The level analysis used is the group level. This research shows that SERUNI has reclaimed land rights in Kandis and Pangalengan as the results of BOOM program they took a part in. However, SERUNI and APWLD have also struggled in reaching their goals due to the problems they were facing. SERUNI's problems are caused by limited funds and their antagonistic relations with the government and companies. Keywords: SERUNI, APWLD, women workers, women's labour rights, Transnational Advocacy Network (TAN).